Metodologia para detecção de analitos em água com técnicas de espectroscopia ótica em substrato sólido - Hornung, Felipe (2020)
This work presents a technique for the development of a solid substrate for Raman spectroscopy, coupled with the SERS (Surface Enhanced Raman Scattering) effect, using rhodamine 6G as a probe analyte. Throughout the work, a silver nanoparticles synthesis methodology was presented, which are used to amplify the Raman scattering signal through the phenomenon known as SERS, in which metallic nanoparticles in contact with the analyte cause an intensification of the electromagnetic field. Besides, several parameters involved in the solid substrate analysis process were studied, such as the filtering membrane, the microscope objectives, the drying process, the integration time, the colloidal solution pH and the analyte concentration, in order to develop an efficient methodology. For these analysis, besides the solid substrate SERS spectroscopy, ultraviolet-visible spectroscopy and liquid substrate SERS techniques were used. The results show that the SERS spectra obtained in solid substrate presented enhancements about 15x higher than the enhancements obtained in liquid substrate for the same sample. In addition to tests involving rhodamine 6G as a probe analyte, tests were also performed with glyphosate herbicide. For both analytes, the signal to noise ratios in the spectra were 11.2 for 0.0021 mg/L of 6G rhodamine and 3.8 for 3 mg/L of glyphosate, showing that such concentrations are above the detection limit of the technique (signal to noise ratio greater than 3) and can be effectively measured.